Molecular mechanisms controlling μ-opioid receptor activation - Batista Gondin, Arisbel (2019)
The μ-opioid receptor (MOP) is a G protein-coupled receptor (GPCR) responsible for mediating the analgesic effects of opioids such as morphine. Despite the numerous adverse effects associated with opioids, the MOP is the main therapeutic target for the treatment of severe and chronic pain. Due to the current ‘opioid epidemic crisis’ within western societies, extensive research and drug discovery efforts are aiming at the generation of new opioid drugs with improved therapeutic windows. In this context, bias agonism towards the G protein pathway and away from the β-arrestin2 pathway is currently being exploited for the development of safer and more effective MOP-targeted analgesics.